Methionine ameliorates intestinal injury in senescence-accelerated mouse prone-8 mice by reducing sulfate-reducing bacteria and enhancing barrier function - Wu, Ying; Zhang, Yong; Zhou, Min; Liu, Peng; Rao, Xin; Zhang, Yong; Mi, Mantian (Frontiers in Nutrition, 2025)
ObjectiveAge-related intestinal barrier dysfunction is a key factor leading to systemic inflammation. Previous studies have found that methionine and its metabolites play a role in anti-aging, but the specific effects on the intestines of aging mice remain unclear. This study aims to explore the effects of different doses of methionine in the diet on intestinal integrity and gut microbiota, and to clarify its potential mechanism in a mouse model of accelerated aging (SAMP8).MethodSAMP8 mice were selected and divided into three groups, each receiving a Methionine-restricted diet (0.17%Met), normal (0.86%Met), or Methionine-supplemented diet (1.64%Met) for 4 weeks. And SAMP1 mice were used as the control. The intestinal barrier function was evaluated by detecting the levels of LPS, IFABP and Zonulin in serum through ELISA. The integrity of colon tissue, the expression of tight junction proteins (ZO-1 and Occludin) and inflammatory signaling pathways (TLR4/NF-κB) were evaluated by histology, immunofluorescence and Western blot. The composition of the gut microbiota was analyzed by 16S rRNA sequencing, and the levels of hydrogen sulfide (H₂S), sulfomucin in the intestine and the expression of genes related to mucus sulfation were quantitatively detected.ResultMethionine-supplemented diet (1.64%Met) significantly improved intestinal aging. Specifically, it is manifested as reducing the expression of cellular senescence markers p16 and p21, lowering the levels of LPS, IFABP and zonulin in serum, restoring the disordered colon structure, and upregulating the expression of tight junction proteins (ZO-1, Occludin). The pro-inflammatory effect of a methionine-supplemented diet on the TLR4/NF-κB pathway reduces the production of H₂S in the intestine. In addition, Methionine-supplemented diet reshaped the gut microbiota, increasing the abundance of beneficial bacterial genera (such as Parabacteroides) while reducing the abundance of H₂S-producing bacteria (such as norank_f__Desulfovibrionaceae). This change in the microbial community is closely related to the concentration of methionine intake and also associated with the recovery of intestinal sulfation, manifested as an increase in the expression of sulfattransferases (such as Papss2) and an increase in the production of sulfomucin. On the contrary, a methionine-restricted diet increased the abundance of norank_f__Desulfovibrionaceae, exacerbating gut microbiota imbalance and barrier dysfunction.ConclusionA methionine-supplemented diet within the safe range significantly alleviates aging-induced intestinal barrier dysfunction by regulating the gut microbiota, inhibiting H₂S-producing bacteria, and restoring the host’s intestinal sulfation capacity. A new microbiota- sulfation axis pathway was revealed, which promotes the metabolism of toxic sulfur substances related to the microbiota (such as H2S, indoxyl sulfate, etc.), and methionine supplementation was proposed as a promising nutritional strategy to promote intestinal health and alleviate aging-related pathological changes.